The prevalence of injuries in professional Turkish soccer players - Yamaner, F.; Gümüsdag, H.; Kartal, A.; Gümüs, M.; Güllü, A.; Imamoglu, O. (Biomedical Human Kinetics, 2011)
Study aim: To assess the prevalence and anatomical sites of injuries in professional soccer players in one game season.